INTEGRATING UAHPL-DA SYSTEMS WITH VLSI DESIGN TOOLS TO SUPPORT VLSI DA COURSES - Sait, Sadiq M. (1992)
Because of rapid growth in areas related to digital design automation (DA) of very large scale integration (VLSI) systems, it has become necessary to introduce related courses into the university curriculum. In order to support effective teaching and laboratory courses, it is essential to have a complete operational environment established with the help of state-of the-art tools. In this paper, we explain the establishment of such an environment, which is accomplished with the integration of two systems: 1) a DA system which automatically produces VLSI layouts of digital systems modeled in Universal Hardware Programming Language (UAHPL); and 2) a set of VLSI tools, which in addition to several other functions can be used for simulation and verification of layout designs. Compared with other approaches, the integrated DA system provides a very simple user interface, fast turnaround time, no restriction on the final structure of the layout, and simulation and verification of all phases of design. The new environment, called UAHPL-based VLSI DA, is excellent for teaching and research at universities.